PEMBERDAYAAN MASYARAKAT DESA SANDIK MELALUI PENGENALAN INSTALASI MODUL SURYA SEBAGAI SUMBER ENERGI LISTRIK DALAM MENDUKUNG PROGRAM DIVERSIFIKASI ENERGI - Muljono, Agung Budi; Nrartha, I Made Ari; Ginarsa, I Made; Yadnya, Made Sutha; Sasongko, Sudi Mariyanto Al; Sultan, Sultan; Harjian, Muhammad Rivaldi; Tohri, M.; Alfandi, Ahmad Nova (Jurnal Pepadu, 2024)
Technological advances in the energy sector, especially electricity, are needed to utilize clean and renewable energy sources towards net zero emissions. This condition supports the use of new, renewable energy (EBT) by the government and society. Together with Mitra (head of Sandik village), the Mataram University Lecturer Community Service Program team will carry out community empowerment in the field of EBT by socializing Presidential Decree No. 5 of 2006 concerning KEN and PP no. 112 of 2022 concerning Accelerating the Development of EBT to supply electrical energy providers as well as introducing solar module installations as a source of electrical energy to support the energy diversification program. The methods used are presentation, discussion, pre-test, post-test, practice, use of solar energy measuring instruments and presentation on installing solar modules as an electricity source. The implementation of this PkM activity was assisted by students majoring in electrical engineering, electrical systems and equipment from Sandik Village. There were 21 men and 9 women taking part in the PkM. The results of the achievement evaluation mean pre-test score to post-test score increased from 49.725 to 72.0375, an average increase of 44.87%. The community's interest in using PLTS as a source of electricity shows the enthusiastic participation of the Sandik village community.